2005
DOI: 10.1116/1.2006131
|View full text |Cite
|
Sign up to set email alerts
|

Effect of film thickness and annealing temperature on the carbon induced interfacial charge of tetraethoxyorthosilicate based oxide films on p-type Si(100)

Abstract: Articles you may be interested inLow temperature direct bonding mechanisms of tetraethyl orthosilicate based silicon oxide films deposited by plasma enhanced chemical vapor deposition J. Appl. Phys. 112, 063501 (2012); 10.1063/1.4752258 H-induced effects in luminescent silicon nanostructures obtained from plasma enhanced chemical vapor deposition grown Si y O 1 − y : H ( y > 1 ∕ 3 ) thin films annealed in ( Ar + 5 % H 2 ) Annealing and oxidation of silicon oxide films prepared by plasma-enhanced chemical vapor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 31 publications
0
2
0
1
Order By: Relevance
“…It has been reported that it is possible to alter the electrical properties of the interface by changing the interfacial charge concentration of TEOS-based oxide films on silicon [13][14][15]. Carbon is routinely introduced into the deposited oxide film due to the organic nature of the TEOS molecule.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that it is possible to alter the electrical properties of the interface by changing the interfacial charge concentration of TEOS-based oxide films on silicon [13][14][15]. Carbon is routinely introduced into the deposited oxide film due to the organic nature of the TEOS molecule.…”
Section: Resultsmentioning
confidence: 99%
“…37 Torres et al reported bulk and interfacial carbon concentrations in TEOS films before and after annealing in oxygen at 1070°C. 38 The bulk carbon concentration before anneal was 6 ϫ 10 18 cm −3 . The bulk carbon concentration in a 1 m thick layer after anneal decreased to 2.2ϫ 10 18 cm −3 , while the interfacial carbon concentration increased to 1.5ϫ 10 21 cm −3 .…”
Section: Formation Mechanismsmentioning
confidence: 99%
“…Nas curvas, são observados picos característicos de espécies OH na região compreendida entre 3500 e 3800 cm -1[40],[41]. A presença destas espécies reforça o fato da incorporação de subprodutos de TEOS durante a deposição dos filmes.…”
unclassified